THE SALE IN THE MOBILE COMMUNICATION SERVICES (Islamic Sciences Journal, 2023)
In the name of God Deals with the subject of my research , on what transactions telephone service , not the verdicts through telephone service , As well as the concept of financial , and fiscal side in this service.As for the issue of buying and selling , and leasing . The researcher reached , fact that telephony service , not… to the concepts of leasing and making only . The researcher types of transactions in some detail .After his conception of the fact that the making is considered the impact of the caller through the use of this system and this effect is the important thing which is the axis provisions of current transactions whereby . Also of important topics address  , by the researcher question of truth , and metaphor , and what applicable to them .The plan   included the message and detectives following chapters :-  An introduction .-  The first section , is concerned with the doctrinal provisions , and the concept of sales in the transactions telephone service .- The second section , is about the nook of sales in the transactions telephone service-The third section about  The indications .- The result of research.